Finite Element Analysis of an Active Air-Cooling System on a 30V LiFePO4 Battery for a Home Power Generation System - Lingga Vidya Mandala Putra Nasir; Mohd. Arif Fahmi Bin Rosli (Pusat Riset dan Inovasi Nasional, 2024)
By seeing public awareness of the importance of using renewable energy for the sustainability of their children and grandchildren in the future, it has increased public attraction to sustainable and reliable home power plants. However, there are constraints in the application of sustainable home power generation systems, the integration of lithium iron phosphate (LiFePO4) batteries has become famous for their high energy density and long service life. However, efficient thermal management is essential to maintain performance and extend the life of these batteries. The study focused on optimizing the cooling system layout for 30V LiFePO4 batteries used in home power generation systems. Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA) software are used to design and evaluate cooling systems. The cooling system in power generation plays a crucial role in maintaining the efficiency and safe operation of power plants. Power generation processes, whether they involve fossil fuels, nuclear energy, or renewable sources, typically generate a significant amount of heat that needs to be managed effectively